Whole Exome Sequencing Identified a Novel Biallelic SMARCAL1 Mutation in the Extremely Rare Disease SIOD - Jin, Jing; Wu, Keke; Liu, Zhenwei; Chen, Xiaomin; Jiang, Shan; Wang, Zhen; Li, Weixing (Frontiers in Genetics, 2019)
Schimke immuno-osseous dysplasia (SIOD) is an extremely rare autosomal recessive pleiotropic disease. Although biallelic mutations in SMARCAL1 gene have been reported to be the genetic etiology of SIOD, its molecular diagnosis has been challenging in a relatively proportion of cases due to the extreme rarity. Here, we made a definitive SIOD diagnosis of a 5-year-old girl with an extremely mild phenotype by applying whole-exome sequencing (WES). As a result, a novel maternal mutation (c.2141+5G>A) confirmed to create a novel splice donor site combined with a known paternal mutation (c.1933C>T; p.Arg645Cys) were detected. In addition, previous reported SIOD cases showed excessive enrichment for mutations in the helicase ATP-binding and C-terminal domains of SMARCAL1. Similarly, the novel mutation we identified caused a mutant protein truncated in the SMARCAL1 C-terminus. Interestingly, based on the phenotypic profile, compared to reported cases, the patient in our study exhibited milder symptoms with renal dysfunctions limited to asymptomatic proteinuria, but no neurological signs or recurrent infections. Moreover, we identified 73 SMARCAL1-interacting genes, which formed a significant interconnected interaction network with roles in disease-related pathways such as double-strand break repair via homologous recombination, DNA repair and replication fork processing. Notably, the top 15 SMARCAL1-interacting genes all showed a similar renal temporal expression pattern. Altogether, to our knowledge, the case in this study is the first case diagnosed originally based on a genetic test via WES rather than a characteristic phenotype. The identification of the novel allelic mutation (c.2141+5G>A) extends the phenotypic spectrum of SMARCAL1 mutations and the following bioinformatics analysis presents additional genetic evidence to illustrate the role of SMARCAL1 in SIOD.